2009
DOI: 10.1038/jp.2008.230
|View full text |Cite
|
Sign up to set email alerts
|

Massage with kinesthetic stimulation improves weight gain in preterm infants

Abstract: Objective: The aim of this study was to evaluate the effects of massage with or without kinesthetic stimulation on weight gain and length of hospital stay in the preterm infant.Study Design: A prospective randomized clinical trial was conducted evaluating the effects of massage with or without kinesthetic stimulation (KS) on weight gain and length of stay (LOS) in medically stable premature (<1500 g and/or p32 weeks gestational age) neonates. Infants were randomized either to receive no intervention (control),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 26 publications
8
64
0
14
Order By: Relevance
“…All trials wherein the massage was provided by qualified therapists showed a positive result; that is, the massage group gained more weight than the control and/or sham group [3,6,[11][12][13][14].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…All trials wherein the massage was provided by qualified therapists showed a positive result; that is, the massage group gained more weight than the control and/or sham group [3,6,[11][12][13][14].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
“…Massage therapy in 10 out of the 12 articles consists of a 15 min massage session, which includes tactile stimulation with moderate pressure on the limbs and trunk and kinesthetic stimulation on the four limbs [3,6,[11][12][13][14][15][17][18][19]. The other two massage methods are a 20 min touch procedure adopted by Livingston et al [8] and acupressure and meridian massage adopted by Chen et al [16].…”
Section: Massage Methods and Delivery Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most recent Cochrane reviewed that no significant evidence proofed the affectivity of baby massage intervention to enhance baby weight, but some study showed that by administering the baby massage regularly would stimulate baby's tactile and kinesthetic and increase the baby weight until 53 percent (Gonzalez et al, 2009). Furthermore, the baby who experienced massage intervention regularly compared to a baby in the regular intervention as control group could stay alert and active, less crying, and had lower cortisol levels in salivary gland which indicated relax (Massaro, Hammad, Jazzo, & Aly, 2009). The massage intervention becomes one alternative and solution to improve baby development during the first year period which improved health, nutrition, cognition, overall enhancement of physical, cognitive, and reproductive performance (Ruel, Alderman, Maternal, & Group, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It also promotes the development of children through the active stimulation of the neurological system through the skin (6) , allowing for example, an early discharge in hospitalized children because of diseases due to their premature condition (7) . This latter, thanks to the stimulation of better gastric motility, that would be associated with improved digestion and absorption of food, and therefore, the stimulation of growth (8) .…”
Section: Introductionmentioning
confidence: 99%